QFHSA Fall Conference 1997 - Quebec Federation of Home and School Associations (QFHSA) (1997)

Submission to the Special Joint Committee of the Senate and the House of Commons on the Proposed Amendment to Section 93 of the Canadian Constitution - Quebec Federation of Home and School Associations (QFHSA) (1997)
The Quebec Federation of Home & School Associations Inc., (QFHSA) welcomes the opportunity to present this submission to the Special Joint Committee on the proposed amendment to Section 93, sub-sections (1-4) of the Constitution, 1867, concerning the school system in Quebec.

Minority Parents Excluded from Linguistic School Proposal : AQ - Alliance Quebec (AQ) (1997)

Evaluation of Learning in the English Schools of Québec - Advisory Board on English Education (1997)
This report reviews the existing regulatory guidelines for evaluation of learning. Within that context the Advisory Board reports on the attitudes and perceptions of students, parents and educators, based on an extensive survey of their views. The report concludes with a set of recommendations which can guide further discussion on this vital topic. The Evaluation of Learning - Student, Parent, and Educator Questionnaires. Quantitative Analysis of Results - Final Report follows the recommendations, along with the full text of the Educator Questionnaire.

A Brief to the Minister of Education on the Draft Bill : an Act to Amend the Education Act Submitted by Quebec Federation of Home and School Associations - Quebec Federation of Home and School Associations (QFHSA) (1997)
One of the stated aims of the Home and School movement is to assist in forming public opinion favourable to educational reform and to the advancement of the education of the child. Thus we are pleased to be able to submit this brief to the Minister of Education in response to your invitation for advice on the issue of Governing Boards as outlined in the Draft Bill, An Act to amend the Education Act. This document has been studied with interest by QFHSA's Education Committee. However, since the time allowed for consultation is short and falls in the summer vacation period, QFHSA has been unable to involve the local school associations in drawing up this brief.

Alliance Quebec Submission Presented to the Commission de l'Éducation on Bill 109 - An Act to Amend the Education Act, the Act Respecting School Elections and Other Legislative Provisions - Alliance Quebec (AQ) (1997)
Alliance Quebec welcomes the opportunity to comment on Bill 109 - An Act to amend the Education Act, the Act respecting school elections and other legislative provisions. Alliance Quebec is a forum for Quebec's English-speaking communities; it promotes and protects the concerns of Quebec's minority-language communities: Englishspeaking Quebecers.

1997 Annual General Meeting : Book of Reports - Quebec Federation of Home and School Associations (QFHSA) (1997)

Resolution Adopted by the Executive Committee of Alliance Quebec on April 9, 1997 - Alliance Quebec (AQ) (1997)

Real Dialogue Takes Two Voices, Alliance Quebec Tells Premier Lucien Bouchard - Alliance Quebec (AQ) (1997)

The Integration of the New Information and Communication Techologies in the English Schools of Québec - Advisory Board on English Education (1997)
At a time when the reform of education is under way and there is mounting pressure to integrate the new information and communication technologies in schools, the Advisory Board on English Education has tried to identify some of the opportunities for and barriers to an effective implementation of technological developments, in order to allow English schools to take full advantage of the new technologies for the enhancement of learning. To this end we have focused on the four key elements of the educational process most conducive to change: the role of the teacher, student learning, school organization and the need to expand the present technological network throughout the school system.

Alliance Quebec Supports Linguistic School Boards - Alliance Quebec (AQ) (1997)
AQ_Press_Release_Alliance Quebec supports linguistic school boards_1997.transformed

Reorganization of School Boards Constitutional Amendment - Alliance Quebec (AQ) (1997)

Island Schools - Goodwin, Amanda (1997)

Creating Linguistic School Boards : It Can Be Done Right ; It Can Be Done Now - Hamelin, Michael J.; Weiner, Gerry; Mell, Trent; Johnstone, Darlene; Rabinovitch, Joe; Fogelbaum, Morrie; Housefather, Anthony; Bayne, Edina; Delgado, Pascual (Alliance Quebec (AQ), 1997)